HANDGRIP STRENGTH MEASURED BY THE MEDIAN AND ASSOCIATED FACTORS IN COMMUNITY-DWELLING AGED PEOPLE (REMUNOM, 2026)
Objective: To characterize the distribution of handgrip strength and associated factors among community-dwelling aged people in a capital city in Northeast Brazil. Methodology: This is a cross-sectional study conducted with 85 aged people, which used hand dynamometry (Jamar®) as a marker of functionality, adopting cutoff points based on the median for each sex (31 kgf for men and 20.5 kgf for women). Results: The results suggest that, although handgrip strength (HGS) was above the median in most of the studied population (64.7%), a significant proportion (35.3%) presented reduced strength. The decline in strength showed a significant association with sociodemographic determinants: female sex (p < 0.01), single marital status (p = 0.048), and low family income (p = 0.03). Reduced strength was prevalent among women (83.3%) and individuals with an income of up to R$ 1,518.00 (70%), while men and married older adults concentrated the indices of strength above the median. Clinical and lifestyle variables, such as polypharmacy, comorbidities, and physical activity level, did not show a conclusive association, although normal nutritional status showed a tendency toward strength above the median. Conclusion: Handgrip strength may be influenced by social and biological factors, with a significant concentration of socioeconomic variables impacting functional reserve. These findings reinforce the importance of HGS as an early screening tool in primary care to support actions aimed at delaying functional decline and promoting independence in aging.